Analisis Tegangan pada Jalur Pipa dengan Pemindahan Penopang Akibat Longsor - Sepfitrah; Yoan Perima; Mirfaturiqa (Fakultas Teknik UMRI, 2023)
Landslide that has done in the Chevron, Minas oil field area on 4A-54 pipeline section, resulted the failure at one of pipe supports of 12in and 8in pipe diameter. The Action is planned to remove pipe support number 2 which affected a landslide, and move pipe supports number 1 and 3 that is closer to pipe support number 2. For this reason, action is being taken to redesign the piping system so that the pipe line can function safely. Allowable piping design criteria are used based on the maximum distance between pipe supports and maximum stress based on ASME B31.3 standards not greater than 20,000 Psi. Based on the calculation results, the allowable maximum distance between 12 in pipe supports is 16.064 m. Base on stress simulation, the maximum combined tension and torsion stress on the pipeline at that distance is 17606.44 Psi, 12% less than the allowable stress. The combine stress in the pipe produce displacement of pipe in the x-axis direction of 0.074 m and -0.95o.